Small Slovene firms and strategic information technology usage - Dušan Lesjak (Journal for East European Management Studies, 2000)
The article describes a study, which tries to identify the degree to which information technology is used strategically in Slovene small firms. Slovenia is interesting from small business perspective, because from 1990, when the transformation of its economy started, the number of small business has increased almost 6 times (from almost 6,500 to nearly 35,000 in 1998). In the paper the research model, hypothesis, methods and the research sample are explained, together with the results and discussion. – – In dieser Arbeit wird eine Studie ausgewertet, welche das Ausmaß der strategischen Verwendung von Informationstechnologien in kleinen slowenischen Unternehmen thematisiert. Slowenien ist insofern interessant aus der Perspektive der kleinen Unternehmen, als sich dort seit 1990, dem Jahr, in dem die Transformation der Ökonomie einsetzte, die Zahl der kleinen Unternehmen beinahe versechsfacht hat (von fast 6500 auf beinahe 35000 im Jahr 1998). Im vorliegenden Artikel wird das Forschungsmodell, die Hypothesen, Methoden und Beispiele genauso thematisiert wie die Forschungsergebnisse und ihre Implikationen.
Keywords: 650